Seasonal pattern of abundance of Aedes aegypti (Diptera: Culicidae) in Buenos Aires City, Argentina - Vezzani, D. (2004)
In Buenos Aires, the most crowded city of Argentina, there is a potential risk of dengue virus transmission by the mosquito Aedes aegypti during late summer. The temporal patterns of oviposition activity and abundance of breeding sites of this vector were studied in two cemeteries of the city. Between September 1998 and August 1999, we examined 142 ovitraps weekly and a total of 18,010 water-filled containers. Both study areas showed remarkable differences in the percentages of positive ovitraps (19% vs 8%) and breeding sites (18% vs 1%), but similar temporal abundance patterns. The percentage of breeding sites was higher in summer and autumn than in spring and winter, and the percentage of positive ovitraps was higher in summer than in the other three seasons. Immatures were recorded from the first week of October to the second week of July, and oviposition activity from the third week of October until the end of April. In both cemeteries and with both methodologies the highest infestation levels were registered in March (ovitraps: 41.8% and 20.6%, breeding sites : 39.2% and 3.4%). These highest abundances took place after several months with mean temperatures above 20°C and accumulated rainfalls above 150 mm. A sharp decline in oviposition activity was observed when monthly mean temperature decreased to 16.5°C, and no eggs were found below 14.8°C. Seasonal fluctuation of Ae. aegypti abundances in mid-latitudes like Buenos Aires would allow reduction of the egg mosquito population through the elimination of containers during the coldest months, which are free of adults.